2022
DOI: 10.3174/ajnr.a7502
|View full text |Cite
|
Sign up to set email alerts
|

Application of 7T MRS to High-Grade Gliomas

Abstract: MRS, including single-voxel spectroscopy and MR spectroscopic imaging, captures metabolites in high-grade gliomas. Emerging evidence indicates that 7T MRS may be more sensitive to aberrant metabolic activity than lower-field strength MRS. However, the literature on the use of 7T MRS to visualize high-grade gliomas has not been summarized. We aimed to identify metabolic information provided by 7T MRS, optimal spectroscopic sequences, and areas for improvement in and new applications for 7T MRS. Literature was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 180 publications
0
6
0
Order By: Relevance
“…However, most applications focus on point‐resolved spectroscopy (PRESS) 6 . The most commonly used MRS technique in the clinical setting is proton MRS (1H‐MRS), which can detect many metabolites, including N ‐acetyl‐aspartate (NAA), creatine (Cr), choline (Cho), myo‐inositol (mI), glutamate (Glu), glutamine (Gln), gamma‐aminobutyric acid (GABA), glutathione (GSH), lactate (Lac), lipid (Lip), and also the recently described oncometabolite 2‐hydroxyglutarate (2HG) 7,8 . While 2HG is a specific, and thus, a highly valuable marker of IDH‐mutated gliomas, quantifying anything other than the ratio of Cho/NAA is difficult in a clinical setup without MRS experts, as decisions on acquisition, signal processing, and fitting of resonance peaks affect the results to a greater degree than in conventional MRI.…”
Section: Resultsmentioning
confidence: 99%
“…However, most applications focus on point‐resolved spectroscopy (PRESS) 6 . The most commonly used MRS technique in the clinical setting is proton MRS (1H‐MRS), which can detect many metabolites, including N ‐acetyl‐aspartate (NAA), creatine (Cr), choline (Cho), myo‐inositol (mI), glutamate (Glu), glutamine (Gln), gamma‐aminobutyric acid (GABA), glutathione (GSH), lactate (Lac), lipid (Lip), and also the recently described oncometabolite 2‐hydroxyglutarate (2HG) 7,8 . While 2HG is a specific, and thus, a highly valuable marker of IDH‐mutated gliomas, quantifying anything other than the ratio of Cho/NAA is difficult in a clinical setup without MRS experts, as decisions on acquisition, signal processing, and fitting of resonance peaks affect the results to a greater degree than in conventional MRI.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the emergence of the tumor microenvironment, we now have two targets to aim at: the tumor cells themselves, and the microscopic environment surrounding these cells. Previous studies at 7 T have shown the added value of ultra-high-field (7 T) MRI in characterizing and delineating brain tumors on both structural and metabolic level using high-resolution structural imaging and metabolic imaging techniques, such as MR spectroscopy and chemical exchange saturation transfer (CEST), and it can be expected that 14 T will provide even more potential metabolic biomarkers due to its much increased spatial and spectral resolution [ 78 – 81 ]. However, the tumor microenvironment—and in particular the tumor-associated immune cells, such as TAMs—provides an additional and perhaps even more important imaging target with the advent of immunotherapy as a game changer in oncology [ 82 , 83 ].…”
Section: Research Fieldsmentioning
confidence: 99%
“…Postnatal period, Hypoglycemia [37], Hypoxia [33] and Neuronal Activation [34] Schizophrenia [38], Mitochondrial disorders [39], Tumors [40], Ischemic stroke [35] and Bipolar disorder [41] Glycogen [42] Cognition, memory and glutamateric neurotransmission 7.8 ± 0.3 µmol/g [43] Mainly in Astrocytes Hypoglycemia [44,45] and prolonged exercise [46] Diabetes [47] and Lafora disease [48,49] Ketone bodies [50] Sustain cerebral metabolism briefly 0.25 mM [51] Mainly in Astrocytes Development period, neonates, Prolonged Hypoglycemia and starvation [50,52] Brain injury, AD and PD [50,53] 1.…”
Section: Relevant Metabolic Substrates For Cerebral Metabolismmentioning
confidence: 99%